Study on the Removal of Thiosulfate from Wastewater by Catalytic Oxidation - Al-Khazaal, A. Z.; Ahmad, F.; Ahmad, N. (Engineering, Technology & Applied Science Research, 2019)
Wastewater streaming from industrial plants, including petroleum refineries, chemical plants, pulp and paper plants, mining operations, electroplating operations, and food processing plants, can contain offensive substances such as cyanide, sulfides, sulfites, thiosulfates, mercaptans and disulfides that tend to increase the chemical oxygen demand (COD) of the streams. In the present work, removal of thiosulfate from wastewater by catalytic oxidation using aluminum oxide as a catalyst was studied. Four main factors were considered, namely the initial thiosulfate concentration, the hydrogen peroxide concentrations, the amount of the catalyst and the operating temperatures. The analysis of thiosulfate and sulfate was carried out by using UV Visible Spectrophotometer. An empirical rate equation was developed.